Estimation of yield losses in barley due to Drechslera graminae the causal agent of stripe disease - and G. S. SINDHAN, VIVEK KUMAR, INDRA HOODA (Indian Phytopathology, 2002)
Yield losses in barley varieties C 138 and BG 25 infected by D. graminae [Pyrenophora graminea] were assessed in Haryana, India. Losses were 105.7 and 189.2 kg/ha for C 138 and BG 25, respectively.